Role of the epithelial layer in the generation of superoxide anion by the guinea-pig isolated trachea - G. Sadeghi-Hashjin; P. A. J. Henricks; G. Folkerts; T. Muis; J. Garssen; F. P. Nijkamp (Mediators of Inflammation)
The lucigenin-dependent chemiluminescence generation by guinea-pig isolated tracheal two rings preparations was studied. Tracheal preparations stimulated with phorbol myristate acetate (PMA) or opsonized zymosan generated chemiluminescence. The total amount of chemiluminescence generated in 120 min was 754 ± 63 mV × min for PMA and 4832 ±396 mV × min for zymosan. Generation of chemiluminescence was decreased by more than 50% when the tissues were co-incubated with superoxide dismutase (100 U/ml). Also, addition of direct donors of nitric oxide diminished chemiluminescence generation by zymosan-activated tracheal rings significantly by about 50%. However, the presence of the precursor or of inhibitors of nitric oxide synthase did not influence zymosan-induced chemiluminescence. Removal of the epithelial layer from tracheal rings caused an approximately 90% decrease in chemiluminescence response. However, isolated epithelial cell suspensions did not generate chemiluminescence. Histologic examination showed that the number of eosinophils in the tracheal tissue was reduced from 56 ± 7 to 18 ± 8 per mm basal membrane when the epithelial layer was removed. These results indicated that (1) superoxide anion formation can take place in the guinea-pig trachea, (2) eosinophils in the epithelial and submucosal layers of guinea-pig trachea are likely candidates for superoxide generation although other cell types can also be involved, and (3) besides relaxing airway smooth muscle, nitric oxide donors may also affect superoxide in the airways.